2013
DOI: 10.1088/1748-9326/8/4/044050
|View full text |Cite
|
Sign up to set email alerts
|

Optimally choosing small ensemble members to produce robust climate simulations

Abstract: This study examines the subset climate model ensemble size required to reproduce certain statistical characteristics from a full ensemble. The ensemble characteristics examined are the root mean square error, the ensemble mean and standard deviation. Subset ensembles are created using measures that consider the simulation performance alone or include a measure of simulation independence relative to other ensemble members. It is found that the independence measure is able to identify smaller subset ensembles th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 28 publications
0
66
0
Order By: Relevance
“…Some studies have argued that certain GCMs may not be independent from one another because of shared code or parameterization schemes (Evans et al, 2013;Knutti et al, 2010). In an ensemble of opportunity like CMIP5, this dependence 5 may lead to high-density regions in climate variable space and hence influence the selection of models by methods like Kmeans clustering.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have argued that certain GCMs may not be independent from one another because of shared code or parameterization schemes (Evans et al, 2013;Knutti et al, 2010). In an ensemble of opportunity like CMIP5, this dependence 5 may lead to high-density regions in climate variable space and hence influence the selection of models by methods like Kmeans clustering.…”
Section: Discussionmentioning
confidence: 99%
“…Weighting based on correlations is supposed to remove much of the dependence between models, and thus make the sample more like a sample of independent models. Studies have shown that such a weighting scheme is superior to simple model averaging, with respect to both evaluating uncertainty and improving predictions (Bishop and Abramowitz 2013;Evans et al 2013).…”
Section: Assigning Different Weights To Each Model In a Multi-model Ementioning
confidence: 99%
“…Given the ever-increasing collaborations of geophysical modelling communities in joint assessment studies, MM ensembles are becoming very popular and an opportunity to extend and generalize individual deterministic model results Solazzo and Galmarini, 2014;Galmarini et al, 2004;Vautard et al, 2012;Evans et al, 2013;Bishop and Abramowitz, 2013;and many others).…”
Section: Introductionmentioning
confidence: 99%